Probabilistic approach on the analysis of a Kayabaşı_Ekici type hip prosthesis using approximate solution tecniques - Kayabaşı, Oğuz (My University, 2011)
KAYABAŞI_EKİCİ TİP KALÇA PROTEZİ ANALİZİNE YAKLAŞIK ÇÖZÜM YÖNTEMLERİ KULLANARAK OLASILIKSAL YAKLAŞIMI Sonlu elemanlar metodu, ortopedik aletlerin tasarımında kullanılan en gelişmiş simülasyon tekniği yöntemidir. Bu yöntem kalça protezi tasarımında ve diğer ortopedik cihazların analizi için bir araç olarak kullanılır. Kalça protezi tasarımı, mühendis ve cerrahlar arasında yakın işbirliğini gerektiren karmaşık bir süreçtir. Bir kalça protezi tasarımında en önemli faktörlerden biride femur ve kemik-çimentosuna gelen gerilmeleri azaltmaktır. Bu çalışmanın amacı, yeni bir kalça protezi geliştirerek protezin kemik çimentosunda hastanın yaşam aktivitelerine bağlı olarak zamanla hareket etmesinin engellenmesidir. Bu amaçla kalça protezini ilk olarak parametrik modellenerek analizi yapılmış daha sonra modele olasılıksal yöntem entegre ederek performans analizleri yapılmıştır.

PROBABILISTIC APPROACH ON THE ANALYSIS OF A KAYABAŞI_EKİCİ TYPE HIP PROSTHESIS USING APPROXIMATE SOLUTION TECNIQUES The finite element method, one of the most advanced simulation techniques in solid mechanics, is used for orthopedic biomechanics. It is used as a tool for the design and analysis of total joint replacement and other orthopedic devices. The design of hip joint prostheses is a complex process that requires close co-operation between engineers and surgeons. To design highly durable prostheses one has to take natural processes occurring in bone into account. One of the most important factors in the implant design is to reduce stress on the femur and the bone-cement. The purpose of this study is to investigate the behavior of newly designed implants under body weight load during stumbling by parametric modeling. Two different implant materials have been selected to study appropriate material and fatigue life resistant. In the parametric design, the prosthesis functional requirement is that the locking of stem to the femur head using cement should be strong enough to preclude unlocking during the life time of a patient and to prevent sliding of the implant into the bone-cement. These parameters are then optimized. Using the results of this investigation, the probability of failure was investigated for both the initial and shape-optimized prosthesis designs using several simple performance functions describing fatigue theory (Goodman, Gerber, Soderberg), static and dynamic failure of the cement–prosthesis interface. The optimum geometry and material properties are then compared with Charnley’s implant results.
Keywords: Makine Mühendisliği; Olasılık; Protez